(untitled) (Research, Society and Development, 2020)
Violence against women in all its forms is a phenomenon present in our society and needs to be studied for its best confrontation. This study aims to analyze the cases of interpersonal or self-harm in women through the SINAN notifications of the 16th Regional Health Coordination, from January 2011 to December 2018. This is a quantitative, descriptive, exploratory study. and retrospective that will be held in health regions 29 and 30, with the population composed of women living in the cities belonging to these regions, and the sample composed of women reported for interpersonal / self-harm. Data were collected from the Information Technology Management Department of the State Department of Health, through the public domain Bi Health Portal and analyzed using the SPSS program, version 22.0. The number of notifications has been increasing gradually year after year, the profile of the woman analyzed is white, married / stable union, in the age group of 20 to 29 years and the most common violence suffered and physical, followed by psychological. The gradual increase in cases of violence highlights the need to act otherwise, seeking different solutions to what has already been done.